Respuesta :
Whenever you're solving for a system of equations, you always set what y is equal to on both sides equal to each other.
So,
y = -x + 2
y = 3x - 4
-x+2 = 3x - 4
Ans: -x+2 = 3x-4
So,
y = -x + 2
y = 3x - 4
-x+2 = 3x - 4
Ans: -x+2 = 3x-4
Answer:
Option C is correct
−x + 2 = 3x − 4
Step-by-step explanation:
Given the system of equations:
Equation H: y = −x + 2 ......[1]
Equation J: y = 3x − 4 .....[2]
To find the solution to the set of equations.
Equation equation [1] and [2] we have;
[tex]-x+2 = 3x-4[/tex]
Add x to both sides of an equation:
[tex]2 = 4x-4[/tex]
Add 4 to both sides we have;
[tex]6= 4x[/tex]
Divide both sides by 6 we have;
[tex]x = \frac{3}{2}[/tex]
Substitute in [1] we get;
[tex]x = \frac{1}{2}[/tex]
Solution = [tex](\frac{3}{2}, \frac{1}{2})[/tex]
Therefore,the following steps can be used to find the solution to the set of equations is:
−x + 2 = 3x − 4